Energy conservation performance of a solar thermal and seasonal thermal energy storage-based renewable energy convergence system for glass greenhouses - Min-Hwi Kim; Deuk-Won Kim; Dong-Won Lee; Jaehyeok Heo (Case Studies in Thermal Engineering, 2023)
The utilization of renewable energy sources have gained significant attention in recent years for greenhouse that consumed lots of cooling and heating energy. This study investigated a solar thermal and seasonal thermal-based renewable energy convergence system. This system consists of a solar thermal system, tank- and borehole-type seasonal thermal energy storage, multi-source (i.e., air and water) heat pumps, and ground-source heat pumps. The detailed control logic of the proposed system was implemented, and the system was constructed in a test greenhouse at the Purme Yeoju Farm in South Korea. During the cooling season, the multi-source heat pumps were operated as air-source heat pumps, which showed a coefficient of performance (COP) only 0.5 less than that of the ground source heat pump. The efficiency of the solar thermal system was determined to be 36.6% throughout the investigation period, and the heat storage efficiency of the tank-type seasonal thermal energy storage was 75.7%. Consequently, the proposed system showed a COP of 2.9 during the heating season. The proposed system shows that over 70% of the operating energy can be saved, which is unachievable when using conventional electric heaters.